This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using the arctangent addition formula , we see that
arctan ( 2 k 2 1 ) = arctan ( 4 k 2 2 ) =
arctan ( 1 + ( 2 k + 1 ) ( 2 k − 1 ) ( 2 k + 1 ) − ( 2 k − 1 ) ) = arctan ( 2 k + 1 ) − arctan ( 2 k − 1 ) .
Summing from k = 1 to k = n , we have
( arctan ( 3 ) − arctan ( 1 ) ) + ( arctan ( 5 ) − arctan ( 3 ) ) + ( arctan ( 7 ) − arctan ( 5 ) ) +
. . . . + ( arctan ( 2 n − 1 ) − arctan ( 2 n − 3 ) ) + ( arctan ( 2 n + 1 ) − arctan ( 2 n − 1 ) ) .
As can be seen, this is a telescoping sum, with terms canceling pairwise, leaving us
with arctan ( 2 n + 1 ) − arctan ( 1 ) . The given limit then becomes
lim n → ∞ ( arctan ( 2 n + 1 ) − arctan ( 1 ) ) = 2 π − 4 π = 4 π .